Don’t Keep My UDFs Hostage - Exporting UDFs For Debugging Purposes - Holanda, Pedro; Raasveldt, Mark; Kersten, Martin (Anais do Simpósio Brasileiro de Banco de Dados (SBBD); 2017: Anais do XXXII Simpósio Brasileiro de Bancos de DadosDO - 10.5753/sbbd.2017.174636, 2017)
User-defined functions (UDFs) are an integral part of performing in-database analytics. Executing data analysis inside a database provides significant improvements over traditional methods, such as close-to-the-data execution, low conversion overhead and automatic parallelization. However, UDFs have poor support for debugging. Since they are executed from within the database process, traditional debugging tools such as Integrated Development Environments (IDEs) and Read-Eval-Print Loops (REPLs) cannot be used during development. As a result, writing functional UDFs is challenging. In this paper, we present an extension to the open-source database system MonetDB that allows developers to debug their UDFs using modern debugging techniques.